Biodiversity education: resources and sources used by school teachers and rangers in Mendoza (Argentina) - Barahona, Alexandra Daiana (2023)
This research had the aim of studying how biodiversity education is practiced in formal andnon-formal settings by primary school teachers and rangers. We explored 1) type of resourcesused by practitioners to prepare a biodiversity lesson plan, 2) sources of materials available atthe school and in protected areas, 3) teaching methods and resources used by teachers in a biodiversity lesson plan. For preparing a class, the teacher mainly uses print and digital resources, whereas rangers prefer to rely on print material and other resources, such as consulting withresearchers, and learning through interaction with local people. While schools receive resourcesfrom government education and environmental agencies, protected areas receive them from academic institutions and environmental agencies. It is necessary to create spaces for them to share educational experiences, join forces and make visiting protected areas a significant part of the longer-term teaching process at school.